Accidents at work: A qualitative study on the main procedural vicissitudes in Portuguese case law - Rebelo, G.; Almeida, A. R. (International Journal on Working Conditions, 2025)
The issue of accidents at work linked to the protection of occupational safety and health has been an international political concern for decades. Despite various advances, statistics on accidents at work (fatal and non-fatal) still show a relatively high incidence in some EU countries, particularly in Portugal. Occupational safety and health issues are at the centre of European social policies and national public policies. The aim of this article is to identify, based on an analysis of Portuguese case law, the most frequent issues relating to accidents at work in the courts. Jurisprudence was analysed and collecting summaries of 330 judgments from the higher courts, the main themes on accidents at work discussed at judicial level in Portugal were identified. This study reveals information that will be important for political decision-makers and social partners in responding to and preventing this important labour problem. It was possible to identify, in terms of frequency, six groups of descriptors (and their respective sub-themes) specifically related to the procedural vicissitudes of accidents at work in Portuguese courts: ‘Proof’ (with 55 frequencies); ‘Liability, reparation and services’ (68 frequencies); ‘Compliance guarantee’ (63 frequencies); ‘Labour Accident Fund (26 frequencies); reporting an accident at work (11 frequencies) and ‘Prescription and forfeiture’ (7 frequencies). The main conclusion/recommendation of this study is that, considering the gap in the literature on the subject, further research is needed into the procedural vicissitudes inherent in labour accident lawsuits in Portugal.